Microbial Agents Causing Infective Corneal Ulcer and their Anti-microbial Susceptibility pattern (Bangladesh Medical Journal, 2019)
This study was designed to identify the microbial agents causing infective corneal ulcer and to carry out the antimicrobial susceptibility patterns of isolated bacteria causing infective corneal ulcer. Out of 80 samples, 67 (83.75%) cases were positive by microscopy and culture. This study showed pure fungal growth in 39 (48.75%) cases, pure bacterial growth in 8 (10%) cases, mixed microbial growth (both fungi and bacteria) in 20 (25%) cases and no growth was observed in 13 (16.25%) cases. Among the fungal isolates, Aspergillus species was the leading agent detected in 37(46.3%) cases followed by Penicillium species in 7 (8.8%) instances. Pseudomonas aeruginosa was the most common bacterial pathogen found in 11 (13.8%) cases followed by Staphylococcus epidermidis present in 9 (11.3%) cases. Gentamicin, Ciprofloxacin and Levofloxacin were found to be better efficacious drugs against most of the bacterial pathogens noted in antimicrobial susceptibility test. This study showed that infective corneal ulcers are caused by both bacterial and fungal agents but fungal agents are more common. The findings of this study would help the ophthal- mologists in evidence based management of their patients of infective corneal ulcer.Bangladesh Med J. 2018 May; 47 (2): 1-6